Development and design of scalable and efficient salt composite materials for low temperature thermochemical energy storage - Haomin, Wang (2024)
This research sets out to develop and characterise the performance of composite materials comprising porous matrices impregnated with salts for low temperature (< 150 ℃) thermal storage applications. In detail, three types of porous matrix, namely microporous zeolite 13X, commercial mesoporous silica (CMS), and macroporous vermiculite, were impregnated with five types of salt (i.e. CaBr2, MgBr2, MgSO4, CaCl2, and Al(NH4)(SO4)2) at different salt loading amounts. In addition, CMS based binary salt composites with the salt combination of hygroscopic salt + large energy storage density salt had been produced and characterised as well. The physicochemical results including texture properties, surface morphology, elemental analysis, and chemical analysis indicated that salt has been successfully impregnated into the porous matrices. The moisture adsorption/desorption tests for different types of composites showed the following results. • Impregnating CaCl2, MgSO4, and Al(NH4)(SO4)2 into zeolite 13X has little or even negative impact on its moisture adsorption/desorption performance. While bromide salts significantly improved the moisture adsorption performance for zeolite 13X. • Commercial mesoporous silica (CMS) based composites with good fluidisation property achieved large moisture adsorption capacity and excellent cyclic thermal stability. • When compared to the single salt composites, the addition of hygroscopic salt for CMS based composites can improve the moisture adsorption capacity, moisture adsorption rate, and modify moisture desorption temperature. It can be noticed that the fluidisable CMS based composites, especially binary salt composites, have achieved good moisture adsorption/desorption performance in the aspects of moisture adsorption capacity, moisture adsorption rate, moisture desorption temperature, and moisture desorption rate. Therefore, they have large potential to be adopted in low-temperature fluidised bed based thermal energy storage systems.